Measuring Discounting without Measuring Utility - Attema, Arthur E.; Bleichrodt, Han; Gao, Yu; Huang, Zhenxing; Wakker, Peter P. (American Economic Review, 2016)
We introduce a new method to measure the temporal discounting of money. Unlike preceding methods, our method requires neither knowledge nor measurement of utility. It is easier to implement, clearer to subjects, and requires fewer measurements than existing methods. (JEL C91, D11, D12, D91)